Eficiencia del transporte férreo de carga Internacional: Un análisis a través de la envolvente de datos (Efficiency of railways international freight: an analysis with data envelopment) - Zamora Torres, América Ivonne; Pedraza Rendón, Oscar Hugo (UANL Facultad de Contaduría Pública y Administración, 2014)
Abstract: In this paper based on the methodology of Analysis of Data Envelopment (DEA), the efficiency is calculated 32 countries with the largest trade flows for 2013. During the first stage, the overall technical efficiency is determined, which is calculating the product of pure technical efficiency and the efficiency of scale. In a second, benchmarking analysis given current inputs and outputs as well as the target was carried out. The results shows that the countries of China, United States, Singapore and Thailand show overall technical efficiency; China, United States, Hong Kong, Japan, Singapore and Thailand have pure technical efficiency and the countries of Brazil, Canada, China, United States, India. Russia, Singapore and Thailand have scale efficiency. With respect to Mexico, although it is not efficient according to the results shown there are different proposals and guidelines to follow which should give priority to the decrease of costs by 62.67 percent to the value of 318.57USD; increase rail infrastructure and pathways electrified by 85.88 percent for each item.